Not all aragonitic molluscs are missing: taphonomy and significance of a unique shelly lagerstatte from the Jurassic of SW Britain - Jordan,N; Allison,PA; Hill,J; Sutton,MD (Lethaia, 2015)
The Blue Lias Formation at Lyme Regis (Dorset, UK) includes an exceptional pavement of abundant large ammonites that accumulated during a period of profound sedimentary condensation. Ammonites were originally composed of aragonite, an unstable polymorph of calcium carbonate, and such fossils are typically prone to dissolution; the occurrence of a rich association of aragonitic shells in a condensed bed is highly unusual. Aragonite dissolution occurs when pore-water pH is reduced by the oxidization of hydrogen sulphide close to the sediment-water interface. Evidence suggests that, in this case, the oxygen concentrations in the overlying water column were low during deposition. This inhibited the oxidation of sulphides and the associated lowering of pH, allowing aragonite to survive long enough for the shell to be neomorphosed to calcite. The loss of aragonite impacts upon estimates of past biodiversity and carbonate accumulation rates. The preservational model presented here implies that diagenetic loss of aragonite will be greatest in those areas where dysoxic-anoxic sediment lies beneath an oxic waterbody but least where the sediment and overlying water are oxygen depleted. Unfortunately, this implies that preservational bias through aragonite loss will be greatest in those biotopes which are typically most diverse and least where biodiversity is lowest due to oxygen restriction.